Hepatocellular carcinoma associated with pregnancy about 2 cases at the gynecological and obstetrical clinic of the Aristide Le Dantec hospital, Dakar, Senegal - Diakhate, Abdoulaye; Gassama, Omar; Diadhiou, Mohamed; Ndour, Simon B.; Wade, Mouhamadou; Diop, Daba; Wade, Adja M.; Niang, Ndama; Guèye, Mame D. N.; Guèye, Mamour; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The objective of our study was to report 2 cases of hepatocellular carcinomas associated with pregnancy followed in our structure and to review the literature. Our patients were 30 and 37-year-old multi-gesture females with chronic unattended viral hepatitis B in whom the diagnosis of hepatocellular carcinoma was made in the third trimester of pregnancy at 31 weeks of amenorrhea and 4 days and at 32 weeks of amenorrhea after the incidental finding of tumor hepatomegaly on abdominal-pelvic ultrasound. The main clinical signs were jaundice and hepatomegaly and paraclinical signs were dominated by hepatic cytolysis and anemia in addition to ultrasound images. Follow-up of pregnancies revealed no particularities. A caesarean section was scheduled at 32 weeks of amenorrhea and 32 weeks of amenorrhea and 3 days allowing the birth of two preterm newborns weighing 1210 and 1500 gm with Apgar scores of 8-10/10 and 7-9/10 respectively at the fifth minute. The immediate post-operative follow-up was simple. However, the maternal-fetal prognosis was poor with the death of both patients in a multi-visceral failure table occurring respectively at 6 weeks and 3 weeks after caesarean section. The newborns had died 8 days after birth. Although rare, these two cases challenge any obstetrician to think about liver cancer in pregnant women, especially those with chronic hepatitis B. Ultrasound examination of the liver, or even better, the MRI, which is more efficient, in order to suspect early on a possible liver cancer. Indeed, early diagnosis and a thorough medical approach are essential for the treatment of HCC in pregnant patients.